MANUFACTURING OF ELECTRICAL DRYER MACHINE FOR FOOD AND FRUIT PRODUCTS - Adhan Efendi; oyok yudiyanto; Ridwan Baharta (Universitas Sultan Ageng Tirtayasa, 2019)
Indonesia is a country with a tropical climate that has two seasons, namely the dry season and the rainy season. In the dry season, sun drying is the most widely used method for agricultural products. In the rainy season, people who open businesses in the food processing sector have difficulty predicting uncertain weather. The community needs solar thermal energy to dry food ingredients in the form of opak, tubers, fruits, etc. In the rainy season, the value of production has decreased. This study aims to create a drying machine that can help people to dry various types of food and fruit products. The research was carried out in several stages, namely field observation, literature study, design, manufacturing, and performance testing. The study states that: (1) the manufacturing process of electrical machine dryer was done in three stages: the initial stage, advanced stage, and the final stage. (2) the trial of an electrical dryer machine was used to dry opak and banana. Data obtained in the form of opak before drying weighs 3.4 ounces and after drying to 2.2 ounces. Whereas the banana before drying weighs 7.3 ounces and after drying to 4.5 ounces; (3) electrical dryer machine is very helpful in the process of drying food processed products in Subang Regency.